Relationship between isokinetic strength of the internal and external shoulder rotators and ball velocity in team handball - Bayios, I. A.; Anastasopoulou, E. M.; Sioudris, D. S.; Boudolos, K. D. (The Journal of Sports Medicine and Physical Fitness, 2001)
The purpose of this study was to examine the relationship between the rotational strength of shoulder and ball velocity in team handball players from various levels. METHODS: Three groups of young healthy, male subjects took part in the experiments: one group of 15 handball players, the best of League A1 scorers, another group of 12 handball players, the best of League A2 scorers and a random sample of 15 physical education students. Each subject was tested on a Cybex II isokinetic dynamometer. The concentric action of the internal and external rotation of the dominant shoulder was examined at 60, 180 and 300 deg/sec. Ball velocity was examined in three types of throw: (a) on the spot, (b) with a cross-over step, and (c) with a vertical jump. Statistical analysis was performed using the Pearson product-moment correlation and one-way analysis of variance. RESULTS: The differences of peak torque values of the internal and external shoulder rotation between the three groups were not statistically significant. The differences between groups regarding ball velocity in all types of throw were statistically significant (p<0.001). The relationship between IR and ER rotation of the shoulder and ball velocity was not statistically significant, except the jump shot. CONCLUSIONS: The main finding of this study was that peak torque of IR and ER of the shoulder was not a good indicator of throwing velocity at any type of throw, except the jump shot, in all subjects, regardless of their throwing ability.